The CRASH trial protocol (Corticosteroid randomisation after significant head injury) [ISRCTN74459797] (BMC Emergency Medicine, 2001)
Abstract Background Worldwide, millions of people are treated each year for significant head injury. A substantial proportion die, and many more are disabled. If short term corticosteroid infusion could be reliably shown to reduce these risks by just a few percent then this might affect the treatment of a few hundred thousand patients a year, protecting thousands from death or long term disability. Study design CRASH is a large simple, placebo-controlled trial of the effects of a 48-hour infusion of corticosteroids on death and on neurological disability, among adults with head injury and some impairment of consciousness. Head injured patients with impaired consciousness who are judged to be 16 years or older are eligible if the responsible doctor is, for any reason, substantially uncertain whether or not to use corticosteroids. Organisation The CRASH trial will determine reliably the effects on death and disability of a short corticosteroid infusion following significant head injury. To detect or refute improvements of only a few percent in outcome, many thousands of acute head injury patients must be randomised between control and steroid infusions. Such large numbers will be possible only if hundreds of doctors and nurses can collaborate in the participating emergency departments. Since they are busy, and working in emergency situations, the trial involves them in almost no extra work: no special investigations or changes to usual management are required, and data collection is absolutely minimal. The trial is on-going and new collaborators are welcome. Further information about the trial is available at http://www.crash.lshtm.ac.uk